2021
DOI: 10.3991/ijet.v16i10.22515
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CATs on Mathematical Thinking and Logical Thinking Among Fourth-Class Scientific Students

Abstract: The aim of the research is to find out the effect of applying classroom assessment techniques (CATs) on both mathematical and logical thinking among fourth-grade scientific students. In pursuit of the research objectives, the experimental method was used, and the quasi-experimental design was used for two equivalent groups, one control group taught in the traditional way and the other experimental taught according to the techniques of classroom structural evaluation. The research sample consisted of (44) stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Several findings have shown that mixed learning improves academic performance, increases enthusiasm, and fosters optimistic attitudes toward mathematics and science learning. Among these studies are the following: a study conducted by [29,30] confirmed the influences of blended learning on the middle school students' outcomes of in the southwest part of Tuekry. The findings showed that the mixed learning setting had generated a significant difference in students' academic achievement, to the benefit of the experimental group.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Several findings have shown that mixed learning improves academic performance, increases enthusiasm, and fosters optimistic attitudes toward mathematics and science learning. Among these studies are the following: a study conducted by [29,30] confirmed the influences of blended learning on the middle school students' outcomes of in the southwest part of Tuekry. The findings showed that the mixed learning setting had generated a significant difference in students' academic achievement, to the benefit of the experimental group.…”
Section: Previous Studiesmentioning
confidence: 99%
“…STEM Education has become a top priority for reforming educational processes that adopt integration between academic subjects, as the cries have risen for this over the past two decades, while the STEM approach has proven its effectiveness after its application, especially in the United States of America in particular [23]. Therefore, at the beginning of the discussion about the integrated STEM entrance, we must know what this entrance is, it reflects the first letters of the four words; science, technology, engineering, and mathematics, it is a pedagogical approach that seeks to integrate teaching and learning of the four fields, it needs environments equipped for this purpose, where students practice activities, research projects, workshops, etc.…”
Section: Stem Entrance To Science Technology Engineering and Mathematicsmentioning
confidence: 99%
“…Other sophisticated methods, such as automated assembly of the user's health data (such as temperature and pulse rates) from wearable like wristbands, have also been used. In the event of a suspected COVID-19 infection, the user is informed and directed to a nearby clinic for a checkup [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%